1988
DOI: 10.1083/jcb.106.6.2191
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of intracellular processing of chondroitin sulfate proteoglycan core protein and other matrix components.

Abstract: Abstract. Pulse-chase labeling techniques are used in conjunction with subcellular fractionation and quantitative immunoprecipitation to define the kinetics of intracellular translocation and secretion of proteoglycan core protein, along with link protein and type II collagen. In embryonic chick chondrocytes the core protein is processed very rapidly, exhibiting a t,~ in both the rough endoplasmic reticulum and golgi region of less than 10 min. Link protein appears to be processed as rapidly as the core protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Previous studies have shown that these two glycosyltransferase activities are localized in different compartments (15,19). Note that galactosylation in N4-expressed protein is evident after chondroitinase treatment, in agreement with the observations that xylosylation is a rate-limiting step in GAG biosynthesis and that, after translocation of the core protein to the Golgi, successive reactions proceed quickly without allowing observation of partial intermediate forms (10). The present results imply that, until the precursor is translocated from the xylosylation-competent compartment to the next one, the core protein cannot be galactosylated, and that translocation requires information inherent in the second lectin exon.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies have shown that these two glycosyltransferase activities are localized in different compartments (15,19). Note that galactosylation in N4-expressed protein is evident after chondroitinase treatment, in agreement with the observations that xylosylation is a rate-limiting step in GAG biosynthesis and that, after translocation of the core protein to the Golgi, successive reactions proceed quickly without allowing observation of partial intermediate forms (10). The present results imply that, until the precursor is translocated from the xylosylation-competent compartment to the next one, the core protein cannot be galactosylated, and that translocation requires information inherent in the second lectin exon.…”
Section: Resultssupporting
confidence: 69%
“…Cell Culture and Transfection-Chondrocytes were prepared from sterna of 15-day-old chick embryos and grown in F12 media with 10% fetal calf serum supplemented with gentamicin at a density of 5 ϫ 10 6 cells per dish as described previously (10). COS-1 cells were grown in Dulbecco's modified Eagle's medium with 10% fetal calf serum at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…An overlapping localisation or an interaction of xylosyltransferase with galactosyltransferase I is possible since a similar antibody preparation to that used in the electron microscopy study described above could immunoprecipitate both xylosyltransferase and galactosyltransferase activities [96]; galactosyltransferase I bound to semipurified and immobilised xylosyltransferase [97] and a subcellular fractionation experiment suggested that both enzymes are present in rough and smooth membranes [98]. It has been proposed that the membrane-bound galactosyltransferase I may help 'dock' a soluble xylosyltransferase/core-protein complex to the Golgi membranes, so allowing further processing and translocation of the core protein to occur [99] (presumably such a soluble form resulting from proteolytic loss of the transmembrane domain). However, since data on xylosyltransferase localisation was performed at different times and in different ways, it is still difficult to come up with a unifying conclusion as to where it is located or with which proteins it may interact.…”
Section: Localisation Of the Xylosyl Transfer Reactionmentioning
confidence: 98%
“…4c). A first-order fit of these data revealed that 3 the core protein had a short intracellular half-life of about -CP 12 min (Campbell & Schwartz, 1988) In a second set of experiments, cultures were preincubated with ascorbate for 3 h, at which time the secretion rates of types II and IX collagen had increased to their maximum (Fig. 3) above.…”
Section: Pg-h Core Protein Translocation and Secretionmentioning
confidence: 99%
“…For example, different secretory proteins are transported out of the RER at markedly different rates but move through the remaining portion of the secretory pathway at similar rates, suggesting that protein translocation from the RER is a selective, rate-limiting step in protein secretion (Mitchell & Hardingham, 1981;Fitting & Kabat, 1982;Lodish et al, 1983;Fries et al, 1984;Fellini et al, 1984;Campbell & Schwartz, 1988). In addition, abnormal secretory proteins resulting from mutations or pharmacological treatments exit the RER very slowly, if at all, indicating that the RER also has the ability to discriminate between normal and abnormal secretory proteins (Jimenez et al, 1974;Jimenez & Yankowski, 1978;Kreis & Lodish, 1986;Gothing et al, 1986;Sifers et al, 1988).…”
Section: Introductionmentioning
confidence: 99%